Building a liveable urban environment: an analysis of post-modernist and Islamic view-points - Md Yassin, Khairil Azhar; Abdulai, Abdul-Mumin (2012)
The purpose of this paper is to analyse comparatively postmodernist and Islamic views on the constituents of a livable urban environment. The 21st century has witnessed an increasing urbanization of human settlements, especially in the emerging economies of the developing world.In the wake of such rapid rate of urbanization, both the physical landscape and social aspect of the urban environment are similarly undergoing rapid transformations. Against this backdrop, the paper seeks to examinethree cardinal and defining features of urbanization. These include urban architecture, urban lifestyle or urbanism and urban violence. Based on its insistence on human reasoning alone, postmodernist urban architecture, for instance, has been heavily critiqued for its lack of socio-cultural and religious infusions.Religious elements of the urban environment appear crucial in the Islamic doctrine. And the lack of which may not qualify an urban environment to be described as livable from Islamic stand-point. For this reason, the authors will discuss thoroughly, from both perspectives, the three important building blocks literally of a livable urban environment, highlighting their similarities and differences. Finally, the concept of an ‘Islamic Urbanism’ will be deliberated as it can be used to fill the gaps in the Western idea of a livable urban environment.